Queer Formalism : The Return - Simmons, William J.; Bogart, Aaron (Berlin : Floating Opera Press, 2021)
Lynch, David ; Sillman, Amy ; Eisenman, Nicole ; Bass, Math ; Del Rey, Lana ; Simmons, Laurie ; Franco Klein, Tania ; Lawler, Louise ; Prager, Alex ; von Trier, Lars ; Mann, Sally ; Simpson, Lorna ; Millett, Kate ; Lange, Jessica ; Lankton, Greer
boek